2018
DOI: 10.1038/s41698-018-0069-7
|View full text |Cite
|
Sign up to set email alerts
|

Superhydrophobic lab-on-chip measures secretome protonation state and provides a personalized risk assessment of sporadic tumour

Abstract: Secretome of primary cultures is an accessible source of biological markers compared to more complex and less decipherable mixtures such as serum or plasma. The protonation state (PS) of secretome reflects the metabolism of cells and can be used for cancer early detection. Here, we demonstrate a superhydrophobic organic electrochemical device that measures PS in a drop of secretome derived from liquid biopsies. Using data from the sensor and principal component analysis (PCA), we developed algorithms able to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 26 publications
2
32
0
Order By: Relevance
“…In both cases, data processing and analysis generate trajectories, the shapes of which are indicative of the time evolution and of the characteristics of the system (Figure 5f). SeOECT devices have been used to evaluate tumors [83]. Since cancerous states are associated with an altered protonation state of the intra/extracellular microenvironment, one can estimate the onset and progression of a cancerous disease from a measurement of the ionic content of a bloodderived cell culture.…”
Section: Organic Electrochemical Transistor Devicesmentioning
confidence: 99%
See 2 more Smart Citations
“…In both cases, data processing and analysis generate trajectories, the shapes of which are indicative of the time evolution and of the characteristics of the system (Figure 5f). SeOECT devices have been used to evaluate tumors [83]. Since cancerous states are associated with an altered protonation state of the intra/extracellular microenvironment, one can estimate the onset and progression of a cancerous disease from a measurement of the ionic content of a bloodderived cell culture.…”
Section: Organic Electrochemical Transistor Devicesmentioning
confidence: 99%
“…Using data from the bio-chip and statistical techniques of analysis, we developed algorithms that segregated tumor patients from non-tumor patients. For the ~30 patients across two independent cohorts, the method identified tumor patients with high sensitivity and 93% specificity [83].…”
Section: Organic Electrochemical Transistor Devicesmentioning
confidence: 99%
See 1 more Smart Citation
“…Circulating tumour cells (CTCs) are cancer cells with a solid tumour origin recognized in the peripheral blood, their standard molecular definition is based on the positive detection of cells with an intact nucleus expressing cytokeratin (CK) but negative for CD45, a white blood cell (WBC) marker [ 4 ]. Moreover, we demonstrated that the secretome produced by cancer BDCs were superimposable to the intratumoral interstitial fluid extract from the primary lesion in the same patient for cytokines and glycan adducts content [ 5 , 6 , 7 ]. In this way, we analyzed here the secretome of BDCs focusing on the cytokines production and the advanced glycation products [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, we demonstrated that the secretome produced by cancer BDCs were superimposable to the intratumoral interstitial fluid extract from the primary lesion in the same patient for cytokines and glycan adducts content [ 5 , 6 , 7 ]. In this way, we analyzed here the secretome of BDCs focusing on the cytokines production and the advanced glycation products [ 7 ]. The analysis of the secretome of blood-derived cultures from cancer patients at different stages of the disease, provides a cross-section of knowledge of the molecules that alternate in production and secretion during the progressive steps of the disease.…”
Section: Introductionmentioning
confidence: 99%